Gender Differences Influence Gender Equality Awareness, Self-Esteem, and Subjective Well-Being Among School-Age Children in China - Li, Yifei; Zuo, Man; Peng, Yirong; Zhang, Jie; Chen, Yiping; Tao, Yingxiang; Ye, Biyun; Zhang, Jingping (Frontiers in Psychology, 2022)
Purpose: The aims were to investigate and analyze the status and influential factors of gender equality awareness, self-esteem and subjective well-being among school-age children with different genders, so as to help schools and teachers effectively carry out gender equality and mental health education for children. Methods: This study investigated 323 school-age boys and girls in Hunan Province, China, with gender equality awareness, self-esteem and subjective well-being, and analyzed the influencing factors of multiple linear regression. A total of 284 valid questionnaires were collected and effective retrieved rate was 87.93%. Results: There was a significant correlation among children's gender equality awareness in all fields, and both boys and girls have the lowest awareness of gender equality in the occupational field. Children's self-esteem and subjective well-being were significantly correlated. Gender equality awareness, self-esteem and subjective well-being of boys and girls have different factors. Androgynous is conducive to the development of school-age children's gender equality awareness and self-esteem. Conclusion: The influential factors of gender equality awareness, self-esteem and subjective well-being of children with different genders are different. Therefore, schools and teachers should carry out gender equality and mental health education according to the psychological characteristics of boys and girls.